Service exports and economic growth in an oil rich economy : a case study of tourism in Trinidad and Tobago - Hosein, Roger (2004)
Explores the issue of causality between tourism export growth and economic growth for Trinidad and Tobago. Outlines the possible avenues through which tourism export growth could positively impact upon economic growth. Details the current state of the Trinidad and Tobago tourism market.